2014
DOI: 10.1128/aac.00020-13
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Human Lactoferrin during Aggregatibacter actinomycetemcomitans-Induced Bacteremia in Lactoferrin-Deficient Mice

Abstract: Aggregatibacter actinomycetemcomitans, a periodontopathogen, has been associated with several systemic diseases. Herein, we report the protective effect of human lactoferrin (hLF) during A. actinomycetemcomitans bacteremia in lactoferrin knockout (LFKO ؊/؊ ) mice. The prophylactic, concurrent, and therapeutic intravenous (i.v.) administrations of hLF significantly cleared the bacteria from blood and organs. Nevertheless, all modes of hLF administration significantly decreased the concentrations of serum proinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…The recovered streptomycin resistant colonies were confirmed by PCR [5]. The hLF (100 μg/g body wt) for the prophylactic treatment was prepared as reported earlier [10]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The recovered streptomycin resistant colonies were confirmed by PCR [5]. The hLF (100 μg/g body wt) for the prophylactic treatment was prepared as reported earlier [10]. …”
Section: Methodsmentioning
confidence: 99%
“…Mice (n=5–8) were euthanized at 6, 12, 48 and 96 h following injection of either S. mutans or hLF or both. The recovered S. mutans were expressed in CFU/ml or CFU/g tissue in three independent experiments and the data were statistically analyzed using one-way ANOVA as described earlier [10]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our studies demonstrated that Lactoferrin knockout (LFKO -/-) mice are more susceptible to A. actinomycetemcomitans-induced periodontal disease and bacteremia [33,34], S. mutans-induced bacteremia [35], and C. albicans induced oral candidiasis [36] when compared to WT or LFKO -/-mice administered human LF.…”
Section: Introductionmentioning
confidence: 99%